‘…and yet there’s still no peace’ Catholic Indigenous Residential Schools in Canada - McKinney, Stephen J. (Journal of Religious Education, 2022)
Pope Francis met representatives of the Indigenous peoples of Canada in Rome in April 2022 and in Canada in July 2022. At these meetings he offered sincere apologies for the ways in which the Catholic Church had colluded with the strategy of cultural assimilation of the Indigenous people in Canada. This was especially abhorrent in the residential schools, operated by the Catholic Church (and other Christian churches), that aimed to ‘evangelise’ and ‘civilise’ the Indigenous children. He emphasised that this was a ‘disastrous error’ and the ‘overall effects of the policies linked to the residential schools were catastrophic’. He was very clear at both meetings that this abuse was ‘incompatible with the Gospel of Jesus Christ’. These Catholic residential schools and the impact of these schools on the Indigenous people are discussed in this article.